Assessing the adoption of digital technologies by brazilian beef cattle farmers - David, Leticia Caroline da Silva (Universidade Federal de São Carlos, 2025)
Beef cattle production plays a pivotal role in global food systems and national economies. Digital technologies offer substantial opportunities to enhance operational management, automate processes, and optimize input use. This dissertation pursues two complementary objectives: (i) to identify the main factors associated with the adoption of digital technologies by feedlot beef cattle producers; and (ii) to examine how, and to what extent, digitalization, human capabilities, marketing capabilities, and supply chain integration are linked to the technical efficiency of Brazilian feedlots. A systematic literature review was conducted to map the global landscape of digital technology adoption in beef and dairy cattle production and to identify potential determinants. Empirically, Multiple Correspondence Analysis and Stochastic Frontier Models were applied to data collected from 238 Brazilian feedlot producers (359 observations) between 2020 and 2023. Results show that dairy producers exhibit higher adoption rates of data acquisition and communication technologies as well as automation, control, and robotics systems, whereas beef producers complement these with information system technologies. Technology adoption is associated with producer characteristics (age, education, access to consultancy) and production features (scale, labor, risk management practices, custom feeding services, and slaughterhouse bonuses). Adoption of digital management software, automated feed distribution sensors, and formal contracting is positively linked to higher technical efficiency. These findings provide empirical evidence to guide policy design and support the diffusion of digital technologies in livestock systems.
Determinantes da adoção de tecnologias de agricultura digital por bovinocultores de corte
Keywords: Adoção de tecnologia; Bovinocultura; Fronteira de produção; Pecuária de precisão; Tecnologias digitais; Beef cattle; Digital technologies; Precision livestock; Production frontier; Technology adoption; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA